2008
DOI: 10.1016/j.jqsrt.2007.09.009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Debye plasma on the ground state energies of exotic systems

Abstract: The effect of plasma environment on the ground state energies of exotic systems ppµ, ddµ and ttµ has been analyzed within a generalized three-body formalism using multi-term correlated basis sets. The Debye screening model of the plasma has been adopted for such a study. The binding energies of p with pµ, d with dµ and t with tµ have been estimated for a range of values of the Debye screening parameters. The systems tend towards instability for increased screening. The effect of particle correlation has been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
4
11
0
Order By: Relevance
“…The energies of the screening-free systems (λ = 0) can be compared with very accurate results due to Frolov [15], Bailey and Frolov [16], Kilic, Karr and Hilico [17] and Kar and Ho [18]. We compared them in our previous paper [12]. Our results agree with them reasonably well.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The energies of the screening-free systems (λ = 0) can be compared with very accurate results due to Frolov [15], Bailey and Frolov [16], Kilic, Karr and Hilico [17] and Kar and Ho [18]. We compared them in our previous paper [12]. Our results agree with them reasonably well.…”
Section: Resultssupporting
confidence: 66%
“…The ground-state energies are plotted in figure 1. Both our previous [12] and present results are used. The present results extend much the range of large λ, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed our computations using a variational Ritz method as described in [14,19]. However, the basis set we used is enlarged in comparison to that of [14,19]. Therefore, we describe it below.…”
Section: Computationmentioning
confidence: 99%
“…In recent years, with the gradual development of plasma technology, the study on the structural properties of atomic and molecular systems under the influence of external environments is one of the hot research areas [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Several studies on the atomic systems under Debye screening and modified Debye screening are reported [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%